Women`s volleyball performance indicators according to age category and teams` final position in international competitions - Marzano-Felisatti, J. M.; Priego-Quesada, J. I.; Guzmán Luján, J. F. (European Journal of Human Movement, 2022)
The aim was to determine which performance indicators show significant differences in connection with age category and team`s level in women's international volleyball. The competitions analyzed were Senior Volleyball Nations League (n= 130 games) and U20 (n= 64 games) and U18 (n= 63 games) World Championships held in 2019. The results obtained in this study showed that in the U18 category there were more errors (8.33, p= .001) and greater serve effectiveness (9.00, p= .001). In U20 there was a huge leap in quality with maximum values in block performance (25%, p= .001) and an increase in attack variables (39%, p= .001) accompanied by a decrease in errors (6.00, p= .001) and serve effectiveness (7.00%, p= .001). In the Seniors category, there was a decrease in block effectiveness (15.00%, p= .001) and an increase in attack performance (13.30, p= .001). In the comparison between levels, more differences were detected when teams were further apart in the ranking, and attack and block effectiveness were the most relevant indicators. Based on the findings of this study, we can determine performance indicators for each age category and level, allowing coaches and technical staff to establish new training strategies for their team`s improvement and success.